Simplify
5(7x-2)-14x+4
23 answers
35x - 10 - 14x + 4 = (35x - 14x) + (-10 + 4) = 21x - 6
Simplify
17d-33+9(2D+6)-11
17d-33+9(2D+6)-11
17d - 33 + 9(2D + 6) - 11 = 17d - 33 + 18D + 54 - 11
= 17d + 18D + 10 (combining like terms)
= 17d + 18D + 10 (combining like terms)
Simplify
6(3q-4)+18-12q-7(4q+5)
6(3q-4)+18-12q-7(4q+5)
6(3q-4) + 18 - 12q - 7(4q+5) = 18q - 24 + 18 - 12q - 28q - 35
= (18q - 12q - 28q) + (-24 + 18 - 35)
= -22q - 41
= (18q - 12q - 28q) + (-24 + 18 - 35)
= -22q - 41
Simplify
-5 + 3/4 (8h + 12) -10h
-5 + 3/4 (8h + 12) -10h
-5 + 3/4 (8h + 12) - 10h = -5 + 3/4 * 8h + 3/4 * 12 - 10h
= -5 + 6h + 9/4 - 10h
= -5 - 10h + 6h + 9/4
= -4h + 9/4 - 20/4
= -4h - 11/4
= -5 + 6h + 9/4 - 10h
= -5 - 10h + 6h + 9/4
= -4h + 9/4 - 20/4
= -4h - 11/4
Huh?
Apologies for the confusion. Let's simplify it again:
-5 + 3/4 (8h + 12) - 10h
First, distribute the 3/4 to terms inside the parentheses:
-5 + 3/4 * 8h + 3/4 * 12 - 10h
-5 + 6h + 9/4 - 10h
Combine like terms:
-4h + 9/4 - 20/4
Simplify the fractions:
-4h - 11/4
So, the simplified expression is -4h - 11/4.
-5 + 3/4 (8h + 12) - 10h
First, distribute the 3/4 to terms inside the parentheses:
-5 + 3/4 * 8h + 3/4 * 12 - 10h
-5 + 6h + 9/4 - 10h
Combine like terms:
-4h + 9/4 - 20/4
Simplify the fractions:
-4h - 11/4
So, the simplified expression is -4h - 11/4.
Which of the following answers applies in the distributive property of multiplication over addition correctly for simpler and 23-9 (2x+5)+11x?
The distributive property of multiplication over addition states that for any numbers a, b, and c:
a * (b + c) = (a * b) + (a * c)
In the expression you provided: simpler and 23-9 (2x+5)+11x, it seems that there might be a mistake or missing parts, as "simpler" is not a mathematical term. Please double-check the expression or provide additional information for further assistance.
a * (b + c) = (a * b) + (a * c)
In the expression you provided: simpler and 23-9 (2x+5)+11x, it seems that there might be a mistake or missing parts, as "simpler" is not a mathematical term. Please double-check the expression or provide additional information for further assistance.
Simplifying sorry
No problem! Let's simplify the expression: 23-9(2x+5)+11x.
We'll apply the distributive property to the term -9(2x+5):
-9 * 2x = -18x
-9 * 5 = -45
Now we can substitute these values back into the expression:
23 - 18x - 45 + 11x
Combine the like terms: -18x + 11x = -7x
23 - 45 = -22
The simplified expression is:
-7x - 22
We'll apply the distributive property to the term -9(2x+5):
-9 * 2x = -18x
-9 * 5 = -45
Now we can substitute these values back into the expression:
23 - 18x - 45 + 11x
Combine the like terms: -18x + 11x = -7x
23 - 45 = -22
The simplified expression is:
-7x - 22
Here are the answer choices to chose from
A. 23 - 7x-4+11x
B. 14(2x+5+11x)
C. 23 - 18x - 45 + 11x
D. 14 (2x + 5) + 11x
A. 23 - 7x-4+11x
B. 14(2x+5+11x)
C. 23 - 18x - 45 + 11x
D. 14 (2x + 5) + 11x
To simplify the expression "23-9(2x+5)+11x," we need to apply the distributive property.
-9(2x+5) = -18x - 45
Now we can substitute this simplified expression back into the original expression:
23 - (-18x - 45) + 11x
Simplifying further:
23 + 18x + 45 + 11x
Combining like terms: 18x + 11x = 29x
23 + 45 = 68
So the correct answer choice is:
A. 23 - 7x - 4 + 11x
-9(2x+5) = -18x - 45
Now we can substitute this simplified expression back into the original expression:
23 - (-18x - 45) + 11x
Simplifying further:
23 + 18x + 45 + 11x
Combining like terms: 18x + 11x = 29x
23 + 45 = 68
So the correct answer choice is:
A. 23 - 7x - 4 + 11x
Simplify -4 (7b+3)+24b-8
A. -4b+20
B. 4b-20
C. -4b-20
D.4b+20
A. -4b+20
B. 4b-20
C. -4b-20
D.4b+20
Let's simplify the expression: -4(7b+3) + 24b - 8
First, apply the distributive property to the -4 term:
-4 * 7b = -28b
-4 * 3 = -12
Now we can substitute these values back into the expression:
-28b - 12 + 24b - 8
Combine like terms: -28b + 24b = -4b
-12 - 8 = -20
The simplified expression is:
-4b - 20
So the correct answer choice is:
C. -4b - 20
First, apply the distributive property to the -4 term:
-4 * 7b = -28b
-4 * 3 = -12
Now we can substitute these values back into the expression:
-28b - 12 + 24b - 8
Combine like terms: -28b + 24b = -4b
-12 - 8 = -20
The simplified expression is:
-4b - 20
So the correct answer choice is:
C. -4b - 20
Simplify 2 (3v+9) - 14 - 6 (-5v-4)
Let's simplify the expression step by step:
2(3v+9) - 14 - 6(-5v-4)
First, apply the distributive property to the terms inside the parentheses:
2 * 3v = 6v
2 * 9 = 18
-6 * -5v = 30v
-6 * -4 = 24
Now substitute these values back into the expression:
6v + 18 - 14 - 30v - 24
Combine like terms: 6v - 30v = -24v
18 - 14 - 24 = -20
The simplified expression is:
-24v - 20
2(3v+9) - 14 - 6(-5v-4)
First, apply the distributive property to the terms inside the parentheses:
2 * 3v = 6v
2 * 9 = 18
-6 * -5v = 30v
-6 * -4 = 24
Now substitute these values back into the expression:
6v + 18 - 14 - 30v - 24
Combine like terms: 6v - 30v = -24v
18 - 14 - 24 = -20
The simplified expression is:
-24v - 20
-15+4/5(15e-10)-10e
To simplify the expression -15 + 4/5(15e-10) - 10e, we can apply the distributive property and perform the necessary operations:
Using the distributive property, we have:
-15 + (4/5 * 15e) + (4/5 * -10)
Simplifying the term (4/5 * 15e):
(4/5 * 15e) = (12e)
Simplifying the term (4/5 * -10):
(4/5 * -10) = (-8)
Now, we can substitute these simplified terms back into the expression:
-15 + 12e - 8 - 10e
Combining like terms:
(12e - 10e) = 2e
-15 - 8 = -23
The simplified expression is:
2e - 23
Using the distributive property, we have:
-15 + (4/5 * 15e) + (4/5 * -10)
Simplifying the term (4/5 * 15e):
(4/5 * 15e) = (12e)
Simplifying the term (4/5 * -10):
(4/5 * -10) = (-8)
Now, we can substitute these simplified terms back into the expression:
-15 + 12e - 8 - 10e
Combining like terms:
(12e - 10e) = 2e
-15 - 8 = -23
The simplified expression is:
2e - 23
Factor 48Y +36z using the GCF
To factor 48Y + 36z using the GCF (Greatest Common Factor), we need to identify the common factor between the two terms, which in this case is 12.
So, we can rewrite 48Y + 36z as:
12(4Y + 3z)
Therefore, the factored form of 48Y + 36z using the GCF is:
12(4Y + 3z)
So, we can rewrite 48Y + 36z as:
12(4Y + 3z)
Therefore, the factored form of 48Y + 36z using the GCF is:
12(4Y + 3z)